2019
DOI: 10.2147/ccide.s190092
|View full text |Cite
|
Sign up to set email alerts
|

<p>A retrospective study of oral and maxillofacial pathology lesions diagnosed at the Faculty of Dentistry, King Abdulaziz University</p>

Abstract: Background Oral and maxillofacial lesions (OMFL) comprise a broad spectrum of benign and malignant lesions that affect the oral cavity. However, few epidemiological studies have evaluated oral cavity lesions, and very few have focused on oral soft tissue pathology. The purpose of this study was to identify the prevalence and distribution of OMFL that had been diagnosed histologically at the Oral Pathology Laboratory, Faculty of Dentistry, King Abdulaziz University. Materials and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
44
4
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 17 publications
22
44
4
3
Order By: Relevance
“…When compared to premalignant lesions, malignant neoplastic lesions was much higher (n = 90; 6.5% and 36.8%; respectively). This is an agreement with other authors, [5,7,13] and this suggests failure of early detection of suspicious oral lesions by oral health care providers, delay of case referral from general or specialized dental practitioners to biopsy the lesions or patients being unaware of oral malignant lesions and not seeking treatment in absence of the pain.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…When compared to premalignant lesions, malignant neoplastic lesions was much higher (n = 90; 6.5% and 36.8%; respectively). This is an agreement with other authors, [5,7,13] and this suggests failure of early detection of suspicious oral lesions by oral health care providers, delay of case referral from general or specialized dental practitioners to biopsy the lesions or patients being unaware of oral malignant lesions and not seeking treatment in absence of the pain.…”
Section: Discussionsupporting
confidence: 92%
“…respectively. [7,[15][16][17]] Surprisingly, studies from south western region of Saudi Arabia reported a higher incidence of malignant lesions (38.8%) and smokeless tobacco specifically shamma was held accountable for increased incidence of malignant lesions. [5,18] This higher prevalence of oral cancers might be due to the commonly practiced habits among Yemeni population such as Qat chewing, smoking, and Shamma using, [19] which can contribute to oral cancers, and also could explains the relatively equal reported prevalence of malignant lesions among the presents study sample and that of Saudi study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations